Anticipated changes in soybean drought stress and yield stability under future climates in Northeast China - Jiongchao Zhao; Yixuan Wang; Mingyu Zhao; Daniel Rodriguez; Peter de Voil; Zhihao Tan; Qingquan Chu (npj Sustainable Agriculture)
Abstract Projections of climate change impacts on crop production vary across crops, study areas, and shared socioeconomic pathways indicating a need for higher specificity and regional relevance. Here, we confirmed in silico, future climate warming generally increased soybean yield and yield stability, decreasing the drought stress by mid-century, particularly in the western areas of the Northeast China. The declining yield coefficient-of-variation was mostly caused by both increases in mean yield and decreases in yield standard deviation. The random forest algorithm identified the reduction in the growing degree days during vegetative growth period was the main factor driving higher soybean yields. The increases in rainfall during reproductive growth period and decreases in its coefficient-of-variation would help reduce soybean drought stress and yield coefficient-of-variation in the future. This study highlights regional specific positive impacts of climate change, useful to inform policy and stakeholders to increase preparedness along value chains under expected future climates.